Super-white ceramic plate and preparation process thereof

Through the combination of magnesium oxide modified kaolin and ethylene glycol monovinyl polyvinyl alcohol ether, the bending strength of the ceramic plate and the water absorption rate are improved, and the problems of high cost, low yield and insufficient performance of traditional ceramic plates are solved, and high whiteness is achieved and glossy ceramic plate preparation.

CN119219395AActive Publication Date: 2024-12-31FUJIAN HUATAI GROUP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411341099.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

During the preparation process, traditional white ceramic plates have problems such as high cost, low output and large energy consumption, which are difficult to meet market demand. At the same time, the bending strength and water absorption of ceramic plates are insufficient, which affects its structural stability and waterproof performance.

Method used

Magnesium oxide modified kaolin is used as the base material, and the interface binding force between magnesium oxide and kaolin is enhanced by pretreatment through silane coupling agent, combined with ethylene glycol monovinyl polyvinyl alcohol ether as the binder, and through specific drying and calcination Temperature control forms a dense ceramic structure, improves the bending strength of the ceramic plate and reduces water absorption.

Benefits of technology

The high whiteness, gloss, bending strength and low water absorption of ceramic plates have been improved, reducing costs, and improving the overall performance and market competitiveness of ceramic plates.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The ultra-white ceramic plate comprises a base material, a dispersing agent, a binder and water according to a weight part ratio of (50-60): (2-3): (4-5): (24-30), wherein the base material comprises the following raw materials in parts by weight: 26-30 parts of magnesium oxide modified kaolin, 16-20 parts of quartz powder, 13-15 parts of feldspar powder, 10-12 parts of high-white ball clay, 5-7 parts of dolomite, 6-8 parts of titanium dioxide and 8-10 parts of waste glass. The invention also provides a preparation process of the ultra-white ceramic plate, which comprises the following steps: weighing the base materials, mixing, and crushing the mixed base materials to 400-500 meshes; mixing the base material with a dispersing agent, a binding agent and water to prepare slurry through spheroidizing, performing spray granulation, adding the slurry into a punching machine for punch forming to obtain a ceramic tile blank, drying and firing to obtain the ceramic tile. The invention aims to ensure the whiteness and glossiness of the ceramic plate and improve the bending strength and the water absorption rate at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultra-white ceramic panels, and in particular to an ultra-white ceramic panel and a preparation process thereof. Background Art

[0002] As people's living standards improve, the requirements for home decoration materials are becoming increasingly high-end, environmentally friendly and healthy. As an important part of home decoration, the whiteness, light transmittance and environmental performance of ceramic products have become the focus of consumers. In the preparation process of traditional white ceramic panels, due to the limitations of base material selection and preparation process, there are problems such as high cost, low output and high energy consumption, resulting in high market prices and difficulty in meeting market demand.

[0003] In addition, the whiteness, bending strength, water absorption rate and glossiness of the ceramic panels are important indicators of the products. Ultra-white ceramic panels are made of high-white raw materials and fine processing technology, so that their surface presents extremely high whiteness and has a bright and refreshing visual effect. The bending strength of ultra-white ceramic panels is generally greater than 32MPa. Ultra-white ceramic panels with high bending strength have better structural stability and bearing capacity, and can maintain stable shape and performance in various complex environments. The water absorption rate reflects the weight increase ratio of the ultra-white ceramic panel after absorbing water. Ultra-white ceramic panels with low water absorption have better waterproof performance and durability, and can maintain stable performance in a humid environment. Based on this, the present invention proposes an ultra-white ceramic panel and a preparation process thereof. Summary of the invention

[0004] The purpose of the present invention is to provide an ultra-white ceramic plate and a preparation process thereof, which can improve the bending strength and water absorption rate while ensuring the whiteness and glossiness of the ceramic plate.

[0005] In a first aspect, the present invention provides an ultra-white ceramic plate, comprising a base material, a dispersant, a binder and water in a weight ratio of (50-60): (2-3): (4-5): (24-30); wherein the base material comprises the following raw materials in weight: 26-30 parts of magnesium oxide modified kaolin, 16-20 parts of quartz powder, 13-15 parts of feldspar powder, 10-12 parts of high white ball clay, 5-7 parts of dolomite, 6-8 parts of titanium dioxide, and 8-10 parts of waste glass.

[0006] Furthermore, the preparation method of magnesium oxide modified kaolin comprises: pre-treating magnesium oxide with a silane coupling agent, and then stirring and mixing with ethanol, sodium dihydrogen phosphate and kaolin at a stirring speed of

[0007] 500-600r / min; stirring time is 3-4h, followed by washing, drying at 80-100℃, and calcining at 600-640℃.

[0008] Furthermore, the weight ratio of the pretreated magnesium oxide, ethanol, sodium dihydrogen phosphate and kaolin is (10-12): (80-90): (14-16): (46-50).

[0009] Furthermore, the silane coupling agent is KH550 and KH560 in a weight ratio of 1:(1-2).

[0010] Furthermore, the pretreatment step includes: mixing magnesium oxide, silane coupling agent and ethanol uniformly, and drying at a temperature of 60-80° C. for 5-6 hours.

[0011] Furthermore, the weight ratio of the magnesium oxide, the silane coupling agent and the ethanol is (40-50): (10-14):

[0012] (22-26).

[0013] Furthermore, the dispersant is sodium tripolyphosphate.

[0014] Furthermore, the binder is ethylene glycol monovinyl polyvinyl alcohol ether, with an average molecular weight of 2500-2600 and a hydroxyl value of 16-18 mgKOH / g.

[0015] In a second aspect, the present invention provides a preparation process for an ultra-white ceramic panel, the steps comprising: weighing a base material and mixing it, crushing the mixed base material to 400-500 mesh; mixing the base material with a dispersant, a binder and water with ductile graphite to prepare a slurry, spray granulating it, adding it to a punching machine for punching and forming, obtaining a ceramic tile body, and then firing it after drying.

[0016] Furthermore, the drying temperature is 200-240°C, and the drying time is 2-3 hours; the firing temperature is 1160-1200°C, and the firing time is 1-2 hours.

[0017] The beneficial effects of the present invention are:

[0018] In the present invention, silane coupling agent is first used to pretreat magnesium oxide, thereby enhancing the interfacial bonding force between magnesium oxide and kaolin, so that the modified kaolin can play a better role in the ceramic board; the mechanical properties and chemical stability of kaolin are enhanced by the modification of magnesium oxide, which helps to improve the bending strength of the ceramic board. At the same time, the modified kaolin is more closely combined with other components in the base material, reducing the porosity and thus reducing the water absorption rate.

[0019] In the pretreatment of magnesium oxide in the present invention, KH550 and KH560 complex coupling agents are used as bridge molecules, one end of which reacts with the hydroxyl group on the surface of magnesium oxide, and the other end reacts with the hydroxyl group or oxygen atom on the surface of kaolin, thereby forming a strong chemical bond between the two. The formation of this chemical bond significantly enhances the interfacial bonding force between magnesium oxide and kaolin, so that the modified kaolin can be better dispersed in the ceramic plate and combined with the matrix, thereby improving the overall mechanical strength of the ceramic plate, especially the bending strength. The introduction of the silane coupling agent may also change the hydrophilicity of the kaolin surface to a certain extent, making it more hydrophobic. This change in hydrophobicity also helps to reduce the water absorption rate of the ceramic plate.

[0020] In the present invention, the material is first dried at 80-100°C and then calcined at 600-640°C. Under the two different temperature conditions, the modified kaolin reacts chemically and physically with other raw materials to form a denser ceramic structure. This densified structure reduces the pores and defects inside the ceramic plate, making it more difficult for external forces to destroy the structure of the ceramic plate, thereby improving the bending strength. This denser structure also reduces the formation of pores and naturally reduces the water absorption rate of the ceramic plate. In addition, the drying temperature range of 80-100°C can effectively remove the moisture introduced during the stirring and mixing process, as well as part of the adsorbed water contained in the raw materials themselves. The removal of moisture is a prerequisite for the smooth progress of the subsequent calcination process, because excessive moisture will expand rapidly during the calcination process and may cause the ceramic plate to crack; the slight thermal effect during the drying process may also help promote the initial bonding between the modified magnesium oxide and the kaolin, laying a good foundation for the subsequent calcination process.

[0021] In the present invention, 26-30 parts of magnesium oxide modified kaolin, 16-20 parts of quartz powder, 13-15 parts of feldspar powder, 10-12 parts of high white ball clay, 5-7 parts of dolomite, 6-8 parts of titanium dioxide, and 8-10 parts of waste glass are selected as base materials, which not only ensures the high whiteness and glossiness of the ceramic plate, but also improves the overall performance of the ceramic plate through reasonable mineral composition. In particular, the addition of waste glass not only reduces the cost, but also promotes the densification of the ceramic plate during the firing process through its melting characteristics.

[0022] In the present invention, ethylene glycol monovinyl polyvinyl alcohol ether is used as a binder. Its specific average molecular weight and hydroxyl value enable it to form an effective bonding network in the slurry, thereby enhancing the strength of the ceramic plate body and reducing porosity and water absorption. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] The present embodiment provides an ultra-white ceramic plate, comprising a base material, a dispersant, a binder and water in a weight ratio of 55:2.5:4.5:27; wherein the base material comprises the following raw materials in weight: 28 parts of magnesium oxide-modified kaolin, 18 parts of quartz powder, 14 parts of feldspar powder, 11 parts of high white ball clay, 6 parts of dolomite, 7 parts of titanium dioxide and 9 parts of waste glass.

[0026] The preparation method of the magnesium oxide modified kaolin comprises:

[0027] (1) magnesium oxide, a silane coupling agent and ethanol are uniformly mixed, and dried at 70° C. for 5.5 hours to obtain pretreated magnesium oxide;

[0028] The weight ratio of the magnesium oxide, silane coupling agent and ethanol is 45:12:23; the weight ratio of the silane coupling agent is KH550 and KH560 is 1:1.5;

[0029] (2) The pretreated magnesium oxide is stirred with ethanol, sodium dihydrogen phosphate and kaolin at a stirring speed of 550 r / min and a stirring time of 3.5 h, followed by washing, drying at 90° C., and calcining at 620° C. to obtain the product.

[0030] The weight ratio of the pretreated magnesium oxide, ethanol, sodium dihydrogen phosphate and kaolin is 11:85:15:48;

[0031] Wherein, the dispersant is sodium tripolyphosphate; the binder is ethylene glycol monovinyl polyvinyl alcohol ether, with an average molecular weight of 2550 and a hydroxyl value of 17 mgKOH / g;

[0032] The present embodiment also provides a preparation process of an ultra-white ceramic plate, comprising the following steps: weighing a base material and mixing it, crushing the mixed base material to 450 meshes; mixing the base material with a dispersant, a binder and water to prepare a slurry with ductile graphite, spray granulating the slurry, adding the slurry into a punching machine for punching and forming to obtain a ceramic tile body, drying the slurry at 220° C. for 2.5 hours, and then firing the slurry at 1180° C. for 2.5 hours.

[0033] Example 2

[0034] The present embodiment provides an ultra-white ceramic plate, comprising a base material, a dispersant, a binder and water in a weight ratio of 50:2:4:24; wherein the base material comprises the following raw materials in weight: 26 parts of magnesium oxide-modified kaolin, 16 parts of quartz powder, 13 parts of feldspar powder, 10 parts of high white ball clay, 5 parts of dolomite, 6 parts of titanium dioxide, and 8 parts of waste glass.

[0035] The preparation method of the magnesium oxide modified kaolin comprises:

[0036] (1) Mixing magnesium oxide, a silane coupling agent and ethanol uniformly, and drying the mixture at 60° C. for 5 hours to obtain pretreated magnesium oxide;

[0037] The weight ratio of the magnesium oxide, silane coupling agent and ethanol is 40:10:22; the weight ratio of the silane coupling agent is KH550 and KH560 is 1:;

[0038] (2) The pretreated magnesium oxide is stirred with ethanol, sodium dihydrogen phosphate and kaolin at a stirring speed of 500 r / min and a stirring time of 3 h, followed by washing, drying at 80° C., and calcining at 600° C. to obtain the product.

[0039] The weight ratio of the pretreated magnesium oxide, ethanol, sodium dihydrogen phosphate and kaolin is 10:80:14:46;

[0040] Wherein, the dispersant is sodium tripolyphosphate; the binder is ethylene glycol monovinyl polyvinyl alcohol ether, with an average molecular weight of 2500 and a hydroxyl value of 16 mgKOH / g;

[0041] This embodiment also provides a preparation process of an ultra-white ceramic plate, comprising the following steps: weighing a base material and mixing it, crushing the mixed base material to 400 meshes; mixing the base material with a dispersant, a binder and water with spheroidal graphite to prepare a slurry, spray granulating the slurry, adding the slurry into a punching machine for punching and forming to obtain a ceramic tile body, drying the slurry at 200° C. for 2 hours, and then firing the slurry at 1160° C. for 2 hours.

[0042] Example 3

[0043] The present embodiment provides an ultra-white ceramic plate, comprising a base material, a dispersant, a binder and water in a weight ratio of 60:3:5:30; wherein the base material comprises the following raw materials in weight: 30 parts of magnesium oxide-modified kaolin, 20 parts of quartz powder, 15 parts of feldspar powder, 12 parts of high white ball clay, 7 parts of dolomite, 8 parts of titanium dioxide, and 10 parts of waste glass.

[0044] The preparation method of the magnesium oxide modified kaolin comprises:

[0045] (1) mixing magnesium oxide, a silane coupling agent and ethanol uniformly, and drying the mixture at 80° C. for 6 hours to obtain pretreated magnesium oxide;

[0046] The weight ratio of the magnesium oxide, silane coupling agent and ethanol is 50:14:26; the weight ratio of the silane coupling agent is KH550 and KH560 is 1:2;

[0047] (2) The pretreated magnesium oxide is stirred with ethanol, sodium dihydrogen phosphate and kaolin at a stirring speed of 600 r / min and a stirring time of 4 hours, followed by washing, drying at 100° C., and calcining at 640° C. to obtain the product.

[0048] The weight ratio of the pretreated magnesium oxide, ethanol, sodium dihydrogen phosphate and kaolin is 12:90:16:50;

[0049] Wherein, the dispersant is sodium tripolyphosphate; the binder is ethylene glycol monovinyl polyvinyl alcohol ether, with an average molecular weight of 2600 and a hydroxyl value of 18 mgKOH / g;

[0050] This embodiment also provides a preparation process of an ultra-white ceramic plate, comprising the following steps: weighing a base material and mixing it, crushing the mixed base material to 500 meshes; mixing the base material with a dispersant, a binder and water with spheroidal graphite to prepare a slurry, spray granulating the slurry, adding the slurry into a punching machine for punching and forming to obtain a ceramic tile body, drying the slurry at 240°C for 3 hours, and then firing the slurry at 1200°C for 3 hours.

[0051] Example 4

[0052] The present embodiment provides an ultra-white ceramic plate, comprising a base material, a dispersant, a binder and water in a weight ratio of 50:3:4:30; wherein the base material comprises the following raw materials in weight: 26 parts of magnesium oxide-modified kaolin, 20 parts of quartz powder, 13 parts of feldspar powder, 12 parts of high white ball clay, 5 parts of dolomite, 8 parts of titanium dioxide, and 8 parts of waste glass.

[0053] The preparation method of the magnesium oxide modified kaolin comprises:

[0054] (1) mixing magnesium oxide, a silane coupling agent and ethanol uniformly, and drying the mixture at 60° C. for 6 hours to obtain pretreated magnesium oxide;

[0055] The weight ratio of the magnesium oxide, silane coupling agent and ethanol is 40:14:22; the weight ratio of the silane coupling agent is KH550 and KH560 is 1:1;

[0056] (2) The pretreated magnesium oxide is stirred with ethanol, sodium dihydrogen phosphate and kaolin at a stirring speed of 600 r / min and a stirring time of 3 hours, followed by washing, drying at 100° C., and calcining at 600° C. to obtain the product.

[0057] The weight ratio of the pretreated magnesium oxide, ethanol, sodium dihydrogen phosphate and kaolin is 12:80:16:46;

[0058] Wherein, the dispersant is sodium tripolyphosphate; the binder is ethylene glycol monovinyl polyvinyl alcohol ether, with an average molecular weight of 2500 and a hydroxyl value of 18 mgKOH / g;

[0059] This embodiment also provides a preparation process of an ultra-white ceramic plate, comprising the following steps: weighing a base material and mixing it, crushing the mixed base material to 400 meshes; mixing the base material with a dispersant, a binder and water with spheroidal graphite to prepare a slurry, spray granulating the slurry, adding the slurry into a punching machine for punching and forming to obtain a ceramic tile body, drying the slurry at 240°C for 2 hours, and then firing the slurry at 1200°C for 2 hours.

[0060] Comparative Example 1

[0061] This comparative example provides an ultra-white ceramic plate, comprising a base material, a dispersant, a binder and water in a weight ratio of 55:2.5:4.5:27; wherein the base material comprises the following raw materials in weight: 28 parts of magnesium oxide-modified kaolin, 18 parts of quartz powder, 14 parts of feldspar powder, 11 parts of high white ball clay, 6 parts of dolomite, 7 parts of titanium dioxide and 9 parts of waste glass.

[0062] The preparation method of the magnesium oxide modified kaolin comprises:

[0063] (1) magnesium oxide, a silane coupling agent and ethanol are uniformly mixed, and dried at 70° C. for 5.5 hours to obtain pretreated magnesium oxide;

[0064] The weight ratio of the magnesium oxide, the silane coupling agent and the ethanol is 45:12:23; the silane coupling agent is KH550;

[0065] (2) The pretreated magnesium oxide is stirred with ethanol, sodium dihydrogen phosphate and kaolin at a stirring speed of 550 r / min and a stirring time of 3.5 h, followed by washing, drying at 90° C., and calcining at 620° C. to obtain the product.

[0066] The weight ratio of the pretreated magnesium oxide, ethanol, sodium dihydrogen phosphate and kaolin is 11:85:15:48;

[0067] Wherein, the dispersant is sodium tripolyphosphate; the binder is ethylene glycol monovinyl polyvinyl alcohol ether, with an average molecular weight of 2550 and a hydroxyl value of 17 mgKOH / g;

[0068] The comparative example also provides a preparation process of an ultra-white ceramic plate, comprising the following steps: weighing a base material and mixing it, crushing the mixed base material to 450 meshes; mixing the base material with a dispersant, a binder and water to prepare a slurry with ductile graphite, spray granulating the slurry, adding the slurry into a punching machine for punching and forming to obtain a ceramic tile body, drying the slurry at 220°C for 2.5 hours, and then firing the slurry at 1180°C for 2.5 hours.

[0069] Comparative Example 2

[0070] This comparative example provides an ultra-white ceramic plate, comprising a base material, a dispersant, a binder and water in a weight ratio of 55:2.5:4.5:27; wherein the base material comprises the following raw materials in weight: 28 parts of magnesium oxide-modified kaolin, 18 parts of quartz powder, 14 parts of feldspar powder, 11 parts of high white ball clay, 6 parts of dolomite, 7 parts of titanium dioxide and 9 parts of waste glass.

[0071] The preparation method of the magnesium oxide modified kaolin comprises:

[0072] The magnesium oxide is mixed with ethanol, sodium dihydrogen phosphate and kaolin at a stirring speed of 550 r / min and a stirring time of 3.5 hours, followed by washing, drying at 90°C, and roasting at 620°C to obtain the product. The weight ratio of the magnesium oxide, ethanol, sodium dihydrogen phosphate and kaolin is 11:85:15:48;

[0073] Wherein, the dispersant is sodium tripolyphosphate; the binder is ethylene glycol monovinyl polyvinyl alcohol ether, with an average molecular weight of 2550 and a hydroxyl value of 17 mgKOH / g;

[0074] The comparative example also provides a preparation process of an ultra-white ceramic plate, comprising the following steps: weighing a base material and mixing it, crushing the mixed base material to 450 meshes; mixing the base material with a dispersant, a binder and water to prepare a slurry with ductile graphite, spray granulating the slurry, adding the slurry into a punching machine for punching and forming to obtain a ceramic tile body, drying the slurry at 220°C for 2.5 hours, and then firing the slurry at 1180°C for 2.5 hours.

[0075] Comparative Example 3

[0076] This comparative example provides an ultra-white ceramic plate, comprising a base material, a dispersant, a binder and water in a weight ratio of 55:2.5:4.5:27; wherein the base material comprises the following raw materials in weight: 28 parts of a pretreated magnesium oxide and kaolin mixture, 18 parts of quartz powder, 14 parts of feldspar powder, 11 parts of calcite, 6 parts of dolomite, 7 parts of titanium dioxide and 9 parts of waste glass.

[0077] The preparation method of the magnesium oxide modified kaolin comprises:

[0078] The magnesium oxide, silane coupling agent and ethanol are mixed evenly, and dried at 70° C. for 5.5 hours to obtain the pretreated magnesium oxide;

[0079] The weight ratio of the magnesium oxide, silane coupling agent and ethanol is 45:12:23; the weight ratio of the silane coupling agent is KH550 and KH560 is 1:1.5;

[0080] The weight ratio of the pretreated magnesium oxide to kaolin in the pretreated magnesium oxide and kaolin mixture is 11:48;

[0081] Wherein, the dispersant is sodium tripolyphosphate; the binder is ethylene glycol monovinyl polyvinyl alcohol ether, with an average molecular weight of 2550 and a hydroxyl value of 17 mgKOH / g;

[0082] The comparative example also provides a preparation process of an ultra-white ceramic plate, comprising the following steps: weighing a base material and mixing it, crushing the mixed base material to 450 meshes; mixing the base material with a dispersant, a binder and water to prepare a slurry with ductile graphite, spray granulating the slurry, adding the slurry into a punching machine for punching and forming to obtain a ceramic tile body, drying the slurry at 220°C for 2.5 hours, and then firing the slurry at 1180°C for 2.5 hours.

[0083] Comparative Example 4

[0084] This comparative example provides an ultra-white ceramic plate, comprising a base material, a dispersant, a binder and water in a weight ratio of 55:2.5:4.5:27; wherein the base material comprises the following raw materials in weight: 28 parts of kaolin, 18 parts of quartz powder, 14 parts of feldspar powder, 11 parts of high white ball clay, 6 parts of dolomite, 7 parts of titanium dioxide and 9 parts of waste glass.

[0085] Wherein, the dispersant is sodium tripolyphosphate; the binder is ethylene glycol monovinyl polyvinyl alcohol ether, with an average molecular weight of 2550 and a hydroxyl value of 17 mgKOH / g;

[0086] The comparative example also provides a preparation process of an ultra-white ceramic plate, comprising the following steps: weighing a base material and mixing it, crushing the mixed base material to 450 meshes; mixing the base material with a dispersant, a binder and water to prepare a slurry with ductile graphite, spray granulating the slurry, adding the slurry into a punching machine for punching and forming to obtain a ceramic tile body, drying the slurry at 220°C for 2.5 hours, and then firing the slurry at 1180°C for 2.5 hours.

[0087] Comparative Example 5

[0088] This comparative example provides an ultra-white ceramic plate, comprising a base material, a dispersant, a binder and water in a weight ratio of 55:2.5:4.5:27; wherein the base material comprises the following raw materials in weight: 28 parts of magnesium oxide-modified kaolin, 18 parts of quartz powder, 14 parts of feldspar powder, 11 parts of high white ball clay, 6 parts of dolomite, 7 parts of titanium dioxide and 9 parts of waste glass.

[0089] The preparation method of the magnesium oxide modified kaolin comprises:

[0090] (1) magnesium oxide, a silane coupling agent and ethanol are uniformly mixed, and dried at 70° C. for 5.5 hours to obtain pretreated magnesium oxide;

[0091] The weight ratio of the magnesium oxide, silane coupling agent and ethanol is 45:12:23; the weight ratio of the silane coupling agent is KH550 and KH560 is 1:1.5;

[0092] (2) The pretreated magnesium oxide is stirred and mixed with ethanol, sodium dihydrogen phosphate and kaolin at a stirring speed of 550 r / min and a stirring time of 3.5 h, followed by washing and calcination at 620° C. to obtain the product.

[0093] The weight ratio of the pretreated magnesium oxide, ethanol, sodium dihydrogen phosphate and kaolin is 11:85:15:48;

[0094] Wherein, the dispersant is sodium tripolyphosphate; the binder is ethylene glycol monovinyl polyvinyl alcohol ether, with an average molecular weight of 2550 and a hydroxyl value of 17 mgKOH / g;

[0095] The comparative example also provides a preparation process of an ultra-white ceramic plate, comprising the following steps: weighing a base material and mixing it, crushing the mixed base material to 450 meshes; mixing the base material with a dispersant, a binder and water to prepare a slurry with ductile graphite, spray granulating the slurry, adding the slurry into a punching machine for punching and forming to obtain a ceramic tile body, drying the slurry at 220°C for 2.5 hours, and then firing the slurry at 1180°C for 2.5 hours.

[0096] Comparative Example 6

[0097] This comparative example provides an ultra-white ceramic plate, comprising a base material, a dispersant, a binder and water in a weight ratio of 55:2.5:4.5:27; wherein the base material comprises the following raw materials in weight: 28 parts of magnesium oxide-modified kaolin, 18 parts of quartz powder, 14 parts of feldspar powder, 11 parts of high white ball clay, 6 parts of dolomite, 7 parts of titanium dioxide and 9 parts of waste glass.

[0098] The preparation method of the magnesium oxide modified kaolin comprises:

[0099] (1) magnesium oxide, a silane coupling agent and ethanol are uniformly mixed, and dried at 70° C. for 5.5 hours to obtain pretreated magnesium oxide;

[0100] The weight ratio of the magnesium oxide, silane coupling agent and ethanol is 45:12:23; the weight ratio of the silane coupling agent is KH550 and KH560 is 1:1.5;

[0101] (2) The pretreated magnesium oxide is stirred with ethanol, sodium dihydrogen phosphate and kaolin at a stirring speed of 550 r / min and a stirring time of 3.5 h, followed by washing, drying at 90° C., and calcining at 620° C. to obtain the product.

[0102] The weight ratio of the pretreated magnesium oxide, ethanol, sodium dihydrogen phosphate and kaolin is 11:85:15:48;

[0103] Wherein, the dispersant is sodium tripolyphosphate; the binder is methyl allyl polyoxyethylene ether, and the hydroxyl value is 17 mgKOH / g;

[0104] The comparative example also provides a preparation process of an ultra-white ceramic plate, comprising the following steps: weighing a base material and mixing it, crushing the mixed base material to 450 meshes; mixing the base material with a dispersant, a binder and water to prepare a slurry with ductile graphite, spray granulating the slurry, adding the slurry into a punching machine for punching and forming to obtain a ceramic tile body, drying the slurry at 220°C for 2.5 hours, and then firing the slurry at 1180°C for 2.5 hours.

[0105] The ultra-white ceramic panels prepared in Examples 1-4 and Comparative Examples 1-6 were tested, and the results are shown in Table 1 below:

[0106] Table 1

[0107] Test items Whiteness Bending strength(MPa) Water absorption (%) Glossiness Example 1 95 65 0.11 94 Example 2 95 63 0.12 93 Example 3 92 65 0.13 93 Example 4 94 64 0.12 91 Comparative Example 1 89 60 0.15 89 Comparative Example 2 87 56 0.17 86 Comparative Example 3 90 57 0.18 88 Comparative Example 4 83 53 0.21 84 Comparative Example 5 89 55 0.22 85 Comparative Example 6 90 54 0.20 86

[0108] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. An ultra-white ceramic plate, characterized in that: It includes a base material, a dispersant, a binder and water in a weight ratio of (50-60): (2-3): (4-5): (24-30); wherein the base material includes the following raw materials in weight: 26-30 parts of magnesium oxide modified kaolin, 16-20 parts of quartz powder, 13-15 parts of feldspar powder, 10-12 parts of calcite, 5-7 parts of dolomite, 6-8 parts of titanium dioxide and 8-10 parts of waste glass.

2. The ultra-white ceramic plate according to claim 1, characterized in that: The preparation method of magnesium oxide modified kaolin comprises: pre-treating magnesium oxide with a silane coupling agent, stirring and mixing with ethanol, sodium dihydrogen phosphate and kaolin at a stirring speed of 500-600 r / min; stirring for 3-4 hours, then washing, drying at 80-100° C., and calcining at 600-640° C. to obtain the magnesium oxide modified kaolin.

3. The ultra-white ceramic plate according to claim 2, characterized in that: The weight ratio of the pretreated magnesium oxide, ethanol, sodium dihydrogen phosphate and kaolin is (10-12): (80-90): (14-16): (46-50).

4. The ultra-white ceramic plate according to claim 2, characterized in that: The silane coupling agent is KH550 and KH560 in a weight ratio of 1:(1-2).

5. The ultra-white ceramic plate according to claim 2, characterized in that: The pretreatment step comprises: mixing magnesium oxide, silane coupling agent and ethanol uniformly, and drying at a temperature of 60-80° C. for 5-6 hours.

6. The ultra-white ceramic plate according to claim 5, characterized in that: The weight ratio of the magnesium oxide, the silane coupling agent and the ethanol is (40-50):(10-14):(22-26).

7. The ultra-white ceramic plate according to claim 1, characterized in that: The dispersant is sodium tripolyphosphate.

8. The ultra-white ceramic plate according to claim 1, characterized in that: The binder is ethylene glycol monovinyl polyvinyl alcohol ether, with an average molecular weight of 2500-2600 and a hydroxyl value of 16-18 mgKOH / g.

9. A process for preparing an ultra-white ceramic plate as claimed in claims 1 to 8, characterized in that: The steps include: Weigh the base materials and mix them, crush the mixed base materials into 400-500 meshes; mix the base materials with dispersant, binder and water and spheroidal graphite to prepare slurry, spray granulate, add the slurry into a punching machine for punching and forming to obtain a ceramic tile body, dry and then fire it.

10. The process for preparing an ultra-white ceramic plate according to claim 9, characterized in that: The drying temperature is 200-240° C., and the drying time is 2-3 hours; the firing temperature is 1160-1200° C., and the firing time is 1-2 hours.

Citation Information

Patent Citations

  • Wear-resistant ceramic roller lining plate manufacturing method

    CN107522476A

  • Ceramic material for LED lamp and preparation method thereof

    CN109928764A

  • Low-temperature in-situ synthesis method of nitride whisker coating surface modified cordierite honeycomb ceramic and product prepared by method

    CN115745650A

  • High-whiteness ceramic product and processing technology thereof

    CN115806429A

  • Fiber-reinforced rubber article

    JP2000351856A